Ações de agentes antiinflamatórios e da reserpina no escape renovascular - Forti, Cesar Augusto de Lima e (1984)
The perfusion of the isolated kidney was used to study the effects of dose response curves of NOR in animais (rabbits) pretreated with antiinf1 amatory drugs (AAS and indometacin) and an adrenergic neurone blocker.During the infusion of NOR the preparations reverted partially the vasoconstrictor effect of NOR, in spite of the cbntinued infusion which was named renal vascular escape. Each curve of NOR was studied individually for variations in the renal vascular escape promoted by NOR. During the study of the escape we have studied also the following physiological parameters: perfusion pressure, resistance perfusate flow Rate, urinary flow and the inulin clearance. The first interesting observations was that independent of the previous drug treatment, there was at least a dose of NOR where the escape was observed; in the great majority of the experirnents the esca pes were mui ti pl es through out the spectrum of the dosage leveis. Another fact observed was that the escape responses were the same for the control group and the one infusedwith AAS. The groups treated with reserpine and indomethacin showed significant differences when compared to the control group. There was a decrease in the frequency of escape, and at the same time a decrease in its intensity. A remarcable reduction of the escape,with the use of indomethacin suggests a possible participation of PGs in the reno-vaseu 1 ar process.